2017
DOI: 10.1111/cas.13205
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐cancer stem cell activity of a hedgehog inhibitor GANT61 in estrogen receptor‐positive breast cancer cells

Abstract: Estradiol (E2) increases not only the cell growth but also the cancer stem cell (CSC) proportion in estrogen receptor (ER)‐positive breast cancer cells. It has been suggested that the non‐canonical hedgehog (Hh) pathway activated by E2 plays an important role in the regulation of CSC proportion in ER‐positive breast cancer cells. We studied anti‐CSC activity of a non‐canonical Hh inhibitor GANT61 in ER‐positive breast cancer cells. Effects of GANT61 on the cell growth, cell cycle progression, apoptosis and CSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…48 Estrogen stimulates CSCs activity and expands BCSCs in the ER+cells. 49,50 So, it seems that this model is more compatible with the hormone receptor positive breast cancer cell lines, which should be confirmed with an appropriate animal model and further studies in the future work.…”
Section: Discussionmentioning
confidence: 54%
“…48 Estrogen stimulates CSCs activity and expands BCSCs in the ER+cells. 49,50 So, it seems that this model is more compatible with the hormone receptor positive breast cancer cell lines, which should be confirmed with an appropriate animal model and further studies in the future work.…”
Section: Discussionmentioning
confidence: 54%
“…Inhibitors against Wnt and Hh signaling are under preclinical and clinical tests for TNBC treatment. [163][164][165] Some genomics-based studies continue to shed light on the molecular understanding of TNBC tumorigenesis and heterogeneity and may provide implications for developing TNBCtargeted therapies. [166][167][168][169] Of note, Bartholomeusz et al found that the MEK inhibitor selumetinib inhibits and prevents lung metastasis of TNBC in xenograft models, 170 suggesting that MAPK pathway could be a potential therapeutic target for preventing TNBC lung metastasis.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…A previous study also showed functional interaction between estrogen and Wnt/ß-catenin signaling (Kouzmenko et al, 2004). Estradiol not only stimulates the estrogen signaling pathway but also increases the cancer stem cell (CSC) population in estrogen receptor-positive breast cancer cells (Kurebayashi et al, 2017). Treatment with hormone antagonist in estrogen receptor-positive breast cancer cells may repress their estrogen receptors and be resistant to hormone therapy (Simoes et al, 2015).…”
Section: Discussionmentioning
confidence: 99%